Pengaruh Penerapan Model Connecting Organizing Reflecting Extending Terhadap Pemahaman Konsep Matematika Peserta Didik kelas IX SMP Pembangunan Laboratorium UNP - Dalvi Yenti (Departemen Matematika, 2020)
Conceptual understanding is a basic thing that should be owned by students. Learning process in school is still teacher-centered. Teachers are the ones that active in the class while students are not contributive enough. Thus, student’s understanding is still low. One of ways to increase student’s understanding is by applying learning method named Connecting Organizing reflecting Extending (CORE). The aim of this research is to describe if student’s understanding of math concepts would be better by experiental group or controlled group. This is quasi experiment by using Static Group Design. Based on this research, it is found thant learning process by applying CORE method is better than convensional learning process.Keywords- Understanding of mathematical concepts, connecting organizing reflecting extending learning’s model